Czy industrializacja to wyłącznie męska sprawa? Ziemianki wobec uprzemysławiania majątków w Królestwie Polskim w drugiej połowie XIX i na początku XX wieku - Kostrzewska, Ewelina M. (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Women from landowning class of the Kingdom of Poland were women of so many characters that it had to affect both various areas of everyday lives and industrialization of the properties. Because of economic difficulties strictly connected to changes in the gentry which had place after 1864, some of the women from landed gentry tried tu support men who governed their farms on their own and turned them into profitable, complex enterprises. These country ladies were mainly concentrated on the organization and modernization of female branches of farms. They called it domestic or female industry, as they concentrated there not only on the production but also on the processing. However, these women did not actively participate in the typical male industries such as making of beer or distilling of alcohol. It is also worth mentioning, that although many women deeply interested in their husbands’ and sons’ economic activity, there were also many country ladies who neglected or even dislike this type of action.